Risk factors for the occurrence of new and chronic cases of subclinical mastitis in dairy herds in southern Brazil - Cardozo L.L.* (2015)
© 2015 American Dairy Science Association.The aim of this research was to evaluate the risk factors for new and chronic subclinical intramammary infections (IMI) using the monthly somatic cells count of dairy cows. The study took place at 30 dairy herds with approximately 1,700 cows in lactation. Data characterizing the dairy farms and their milking management were obtained from a survey questionnaire. The somatic cells count values from 2 consecutive months were used to classify cows as either healthy or with new or chronic infections. A chi-squared test was used in the analysis of subclinical IMI to evaluate associations between each independent variable, followed by logistic regression to estimate the risk of a new infection in healthy cows and of chronic infection in cows with new infections. Factors increasing the odds ratio of a cow developing a new case of subclinical mastitis were (1) cows with more than 3 lactations, (2) cows with a mean hyperkeratosis score above 3, (3) cows with the udder below the hock, (4) cows with very dirty udders, and (5) milking of infected animals before healthy cows. Factors increasing the risk of a subclinical chronic infection compared with new cases of subclinical mastitis were (1) a lack of regular maintenance of milking machinery, (2) cows over 100 d in lactation, and (3) cows with the udder on or below the hock. The risk factors identified in this study can be used in IMI control programs to reduce the frequency of new and chronic cases of subclinical mastitis.